POTASSIUM - ARGON AND RUBIDIUM - STRONTIUM SYSTEMS ON THE CONCORDIA DIAGRAM - Levskii L.K.; Morozova I.M.; Savatenkov V.M. (My University, 2001)
In this contribution, we propose using the concordia diagram, which was proposed by Wetherill, to evaluate the discordant values of K-Ar and Rb-Sr mineral ages. The considerable difference between the decay constants of 40K and 87Rb allows us to apply Wetherill's model to these systems.